Physical Activity as a Buffer in the Association Between Perceived Ethnic‐Racial Discrimination and Latinx Adolescent Mental Health - Yuan Zhang; Linda C. Halgunseth (Mental Health Science)
ABSTRACT Latinx adolescents, members of the largest historically minoritized population in the United States (US), experience pervasive ethnic‐racial discrimination, adding extra challenges to this pivotal developmental stage which is marked by significant physical, cognitive, and psychosocial changes. Exposure to ethnic‐racial discrimination is closely connected to their mental health. Physical activity has numerous psychophysiological health benefits, making it a potential yet understudied protective mechanism against the adverse impacts of perceived discrimination. By utilizing data from the Adolescent Brain Cognitive Development (ABCD) Study, the current study examined the buffering effect of physical activity in the association between perceived ethnic‐racial discrimination and mental health in a national sample of Latinx adolescents (N = 1392; Mage = 11.92 SD = 0.66). Findings revealed that longer periods of moderate‐to‐vigorous physical activity exhibited a weaker positive association between perceived ethnic‐racial discrimination and internalizing problems compared to peers who engaged in shorter periods of moderate‐to‐vigorous physical activity, indicating a protective role of physical activity for Latinx adolescents experiencing ethnic‐racial discrimination. This study highlights the importance of promoting moderate‐to‐vigorous physical activity to support resilience and mental health in Latinx youth facing ethnic‐racial discrimination.